Persepsi Anak terhadap Kedekatan Orang Tua dengan Kecerdasan Emosi Remaja - Ayu Metri Wulandari; Nathania Bayu Astrella (Ilmu Psikologi Universitas Yudharta Pasuruan, 2020)
Behaviors that show failure to manage a relationship and interact with the environment and failure to manage and control emotions more often in youth, such as rudeness, abuse of others, even self-injury. One factor that affects the emotional intelligence of a youth is the family environment especially a parent, the teen's perception of a parent's closeness that affects attitudes, views, assessments, and the quality of relationships that grow. This closeness is made by parents and youth essential to shaping emotional intelligence, as parental experience becomes the basis of emotional learning to internalize life. The purpose of this study is to determine if there is a connection between a child's perception of parental closeness and the emotional intelligence of a teen. The population used was 475 high school students, sampling taken with sampling techniques of 21% a total of 100 students. Coefficient validity of the scale of a youth's emotional intelligence is acquired between 0.3307 to 0.6120 and some of its religious coefficiencies. 7391. The child's perception of a parent's closeness scale is between 0.3726 and 0.5912 and the religious coefficiencies of 0.8307. The correlation test shows rxy = 0.4007 with are table 1% = 0.256 and freg = 18,7464 with table 1% = 6.63, the more positive the child's perception of parent proximity, the higher the emotional intelligence.